PID Controller Design for Human Elbow Therapy - Ikbal ESKI; Ahmet KIRNAP; Mehmet KIRNAP (International Journal of Applied Methods in Electronics and Computers, 2016)
A controller design for mechatronic system which capable of doing passive therapeutic exercises of patients who have upper extremity limitation is presented in this paper. Expectation from controller is it should produce torque values can exactly repeat degree values depended on time which were taken from first therapy exercises of patients. The designed controller tested with real angle values which was taken from during elbow therapy. Simulation results showed that the proposed control system has good performance at tracking the therapy trajectory. Also that control system may be used for mechatronic upper limb therapy system which can be produced.